NITROGEN REQUIREMENT OF COMPONENT CROPS IN POTATO + MAIZE INTERCROPPING IN NORTH-WESTERN HILLS OF INDIA - Dua, V K; Kumar, Sushil; Jatav, M K; Lal, S S (Potato Journal, 2015)
A field experiment was conducted to work out the N requirement in potato + maize (1:1) intercropping in North-western hills and to study the effect of nitrogen levels on competition, economics and nutrient balance. The results revealed that maize required only 50% of recommended N while the N dose to potato could not be modified, and it still required 100% N to harness full advantage from potato + maize (1:1) intercropping. The mean maize yield under this treatment was 8.4% higher than ‘expected’, even with only 50% N, while the potato yield was 5.7% higher than ‘expected’. The relative crowding coefficient values of potato (1.12) and maize (1.18) under this treatment also indicated that actual yields of both the crops were higher than the expected yields. Aggressivity values indicated that maize was a dominant species whereas, potato was dominated species when maize was supplied with N (50 or 100%), irrespective of N dose to potato. The competition ratio of potato (0.975) further showed that maize was more competitive than potato when it was supplied with 50% N and potato with 100% N in potato + maize (1:1) intercropping. Results further suggested that economics was also in favour of this treatment as it gave a net return of ` 27,242/- with a B:C ratio of 1.67. There was a positive nutrient balance (93.7 kg N, 43.3 kg P and 121.4 kg K/ha) under this treatment.